Essouk-Tademekka : an early Islamic trans-Saharan market town - Nixon, Sam. (Journal of African Archaeology Monograph Series, 2017)
Essouk-Tadmekka presents the first archaeological exploration of one of the most important market towns on the trans-Saharan camel-caravan routes in the early Islamic period, supplying West African gold, slaves, and ivory to the Mediterranean world. Excavation of Essouk-Tadmekka's ruins - in Saharan West Africa - has enabled Sam Nixon and a team of scholars to better understand this town described by early Arabic geographers, therein providing insights into such wider questions as the origins of trans-Saharan trade, the commerce in gold, and the arrival of Islamic culture in West Africa. This window into the earliest period of trans-Saharan exchange includes illustration of some of the best-preserved ruins along the camel-caravan routes, the earliest-known Arabic writing in West Africa, and rare gold-working remains. Contributors are: Stephanie Black, Sophie Desrosiers, Laure Dussubieux, Thomas Fenn, Dorian Fuller, James Lankton, Kevin MacDonald, Paulo de Moraes Farias, Mary-Anne Murray, Sam Nixon, Thilo Rehren, Peter Robertshaw, Jane Sidell, and Benoit Suzanne.